Integral multidisciplinary approach in a patient with chronic complete spinal cord injury and hip disarticulation - Quinzaños-Fresnedo, J (Spinal Cord Ser Cases, 2015)
STUDY DESIGN: Case report. OBJECTIVES: To highlight the importance of the integral multidisciplinary management of a patient with complete chronic spinal cord injury and hip disarticulation secondary to pressure ulcers (PU). SETTING: Mexico City. METHODS: The case of a 40-year-old male violinist with a spinal cord injury, American Spinal Injury Association Impairment Scale A and neurological level T4, is reported. The patient initiated with bilateral ischiatic, left trochanteric and sacral PU. The ulcers were complicated with infection with sluggish evolution. Thus, it was decided a multidisciplinary management by means of left hip disarticulation and elaboration of a cosmetic prosthesis and the manufacture of a viscous elastic foam cushion for the prevention of new PU. The patient was quickly included in his professional and social activities. CONCLUSION: This study proves that multidisciplinary management of patients with spinal cord injury with complications such as the presence of PU that are resistant to noninvasive treatment can be the solution for the patient’s reintegration into their normal life with adequate quality of life.